ANÁLISE DA LEI Nº 041/2013 DE GUARAPUAVA/PR COM AS LEIS FEDERAIS DE INOVAÇÃO E MARCO LEGAL - KOROCOSKI, LUANA ESTECHE NUNES (2019)
Innovation, science and technology are key pieces for industrial and economic development, as evidenced in most developed countries. Federal Law 13,243 / 2016 brought conceptual changes to innovation, as well as significant changes to the operation of NITs, in the ICT - Company relationship, among others, making municipal innovation laws obsolete. Thus, it was necessary to analyze the provisions of Complementary Law No. 41/2013, of the municipality of Guarapuava, Paraná, as opposed to Federal Law 10,973 / 2004, as amended by Law No. 13,243 / 2016, with a view to a revision and updating accordingly with the current legal framework. As results of the present study, an article published in the journal SODEBRAS was produced in the form of copyright, which carried out a comparative analysis between the complementary law nº 041/2013 of the municipality of Guarapuava with the federal law nº 13.246 / 2016. Also, the studies included in this work contributed to the introduction of Bill 008/2018 by the municipal executive, which resulted in the enactment of Complementary Law 98/2018, characterized by the new law to encourage innovation, scientific research and technological extension, technological extension and technological development in a productive environment in the city of Guarapuava.